Teaching Methodologies and School Organization in Early Childhood Education and Its Association with Physical Activity - Nielsen-Rodríguez, Adriana; Romance-García, Ángel Ramón; Dobado-Castañeda, Juan Carlos (MDPI, 2021)
Early childhood represents a crucial period for child development. Physical activity is essential in this process, but studies show that children are very inactive and do not meet the recommended minimums. Due to the large proportion of time they spend at school, it is necessary to examine active and sedentary behaviors in these environments. The aim of the study is to analyze the amount and intensity of physical activity in preschool children during the school day according to the methodology used. Using accelerometry, the amount and intensity of physical activity and sedentary behavior of 156 children aged 4–6 years at different times of the school day were evaluated. The results revealed that preschoolers spend most of their class time sedentary, with children participating in active methodologies registering the highest amount and intensity of physical activity. Recess and specific motor sessions are the most active times, although the latter should increase the time of intense activity that they imply. To increase physical activity during the school day, it is necessary to establish movement integration methodologies, while increasing the number and adjusting the duration of specific motor sessions and of recesses, so that the maximum possible use is made of them.
Keywords: Educación física para niños; Children; Early childhood education; Physical activity; Sedentary behavior; Movement integration; Active methodologies; Accelerometry